The Development of Practical Learning Guides for Television Broadcasting Management Course - Susy Puspitasari; Dewi Andriyani; Abd Gafur (Postgraduate, University of Mataram, 2023)
This research focuses to produce a learning media which is a guidebook of practical learning and complete practical learning media as well as making students easy in doing practical assignments during attending the online tutorial. This research is a survey study by quantitative approach. The quality of the guidebook and practical learning are viewed through the content validity by the expert and through descriptive analysis taken from the questionnaire given to the college students. The number of experts validating the data in this research is 3 (three) experts. Meanwhile, the number of college students assessing the quality of guidebooks and practical learning media in this research is 23 (twenty-three) college students. The data collection technique in this research used two instruments as product assessment instruments by the expert and college students. The technique of data analysis used two ways include 1) content validity and Aiken Formula verification, and 2) using statistics description. The result of the research shows that; 1) the assessment instrument of guidebook quality and practical learning media have occupied valid criteria with the index Aiken score average, which is 0.76, the result includes in the medium category; 2) the quality of guidebook and practical learning media of television broadcasting management show a good result. This case is based on the result of the descriptive analysis that has been done.